2017
DOI: 10.7759/cureus.1005
|View full text |Cite
|
Sign up to set email alerts
|

A Questionnaire-Based Survey of Physical Medicine and Rehabilitation Residency Training in Pakistan

Abstract: Pakistan is one of the three countries in South East Asia that has an active postgraduate physical medicine and rehabilitation (PM&R) training program. College of Physicians and Surgeons Pakistan (CPSP) offers a four-year structured training program in PM&R. It consists of clinical teaching, lectures, rotations in other specialties, and writing a research dissertation.The aim of this survey was to provide an objective analysis of the current PM&R training program, including the facilities available for trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…For example, in Pakistan some centres are well equipped and have an adequate infrastructure to offer a comprehensive fellowship training for Rehabilitation Medicine. 17 Whereas some other centres lack many important components of post graduate training. However, it is important to consider that training at the post graduate level alone is not sufficient to address the current gaps in neurorehabilitation services.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Pakistan some centres are well equipped and have an adequate infrastructure to offer a comprehensive fellowship training for Rehabilitation Medicine. 17 Whereas some other centres lack many important components of post graduate training. However, it is important to consider that training at the post graduate level alone is not sufficient to address the current gaps in neurorehabilitation services.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was developed by LA, MA and JK after a thorough literature review [5][6][7][8] and was reviewed by two medical education experts for content validity. The survey was piloted among 10 post-graduate residents before putting it to test.…”
Section: Methodsmentioning
confidence: 99%
“…4 Unfortunately, there is a serious dearth of such quintessential research in our country, leading to uneven quality of training with rising stress, maladaptive coping strategies and feeling of abandonment in majority of the trainee doctors. An extensive literature review showed that only a few studies were conducted to identify unrecognized deficiencies of our training programs and that too were either geographically limited to a single centre, city or a province or a single specialty, 3,[5][6][7] leading to results that could not be generalized.…”
Section: Introductionmentioning
confidence: 99%